Running Microsoft Access 97 - Viescas, John L. (Microsoft P. RedmondUS, 1997)
Introduces the basic concepts of Access and summarises the new features in Versions 7 (Access for Windows 95), and 8 (Access 97). Teaches how to design, define and modify database definitions in Access; how to add, delete, and replace data in the database. Looks at designing simple and complex forms and reports, and explains how to link design elements using macro facilities. Provides a companion CD-ROM.